2014
DOI: 10.1002/2014jf003271
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the response of subglacial drainage at Paakitsoq, west Greenland, to 21stcentury climate change

Abstract: Although the Greenland Ice Sheet (GrIS) is losing mass at an accelerating rate, much uncertainty remains about how surface runoff interacts with the subglacial drainage system and affects water pressures and ice velocities, both currently, and into the future. Here, we apply a physically based, subglacial hydrological model to the Paakitsoq region, west Greenland, and run it into the future to calculate patterns of daily subglacial water pressure fluctuations in response to climatic warming. The model is drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…However, this approach limits the focus of these studies to recent seasons for which abundant in situ sensor data exist. In order to examine future scenarios, Mayaud et al (2014) built on the work of Banwell et al (2013) but used a conduit model that includes melt opening and creep closure, driven by a positive degree day runoff model, to examine future changes to year 2095 under various IPCC RCP scenarios (Moss et al, 2010). Those models had hourly or daily resolution and were again limited to the southwest sector of the ice sheet.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, this approach limits the focus of these studies to recent seasons for which abundant in situ sensor data exist. In order to examine future scenarios, Mayaud et al (2014) built on the work of Banwell et al (2013) but used a conduit model that includes melt opening and creep closure, driven by a positive degree day runoff model, to examine future changes to year 2095 under various IPCC RCP scenarios (Moss et al, 2010). Those models had hourly or daily resolution and were again limited to the southwest sector of the ice sheet.…”
Section: Introductionmentioning
confidence: 84%
“…In the southwest sector, Mayaud et al (2014) have bridged the gap spatially between the margin and the interior, and temporally between present and future, using the same runoff and RCP scenarios used in this study. They show that near the margin in the Paakitsoq region, conduits are likely to form earlier, remain longer, and reduce glacier velocity under RCP4.5 and 8.5 compared to present.…”
Section: Increasing Runoff and Vhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested that this occurs through the subglacial drainage system becoming more efficient with increased discharge, thus reducing basal sliding [99,100]. Mayaud et al [101] forced a subglacial hydrological model of the western ice sheet margin in the Paakitsoq region with surface runoff that was derived from climate model output for the RCP2.6, 4.5, and 8.5 scenarios. They showed that as runoff increases in response to a warmer climate, the subglacial drainage system transitions from a less efficient network with associated higher basal sliding to a more efficient network with an associated reduction in basal sliding.…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
“…Lake drainage events are important in opening up moulins, which act as connections between the surface and bed, allowing continued delivery of water through the summer to the subglacial drainage system, facilitating its seasonal evolution and impacting basal water pressures and ice motion over the longer term (Bartholomew et al, 2010;Sole et al, 2013;Tedstone et al, 2013). Increasing amounts of meltwater at higher elevations in the future may allow more lakes to form and drain in those locations, which may lead to an increased hydraulic efficiency of the subglacial drainage system through the formation of channels; however, this is unknown (Mayaud et al, 2014;Leeson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%